Clinical utility of new bone imaging using zero-echo-time sequence in neurosurgical procedures: Can zero-echo-time be used in clinical practice in neurosurgery?. Issue 3 (June 2023) - Inoue, Akihiro; Watanabe, Hideaki; Suehiro, Satoshi; Nishida, Naoya; Shiraishi, Yasuhiro; Furumochi, Taichi; Takimoto, Yoshihiro; Ohnishi, Takanori; Shigekawa, Seiji; Kunieda, Takeharu
Purpose: The purpose of this study was to evaluate the clinical usefulness of zero-echo-time (ZTE)–based magnetic resonance imaging (MRI) in planning the optimum surgical approach and applying ZTE for anatomical guidance during transcranial surgery. Methods: Eleven of 26 patients who underwent transcranial surgery and carotid endarterectomy and in whom ZTE-based MRI and magnetic resonance angiography (MRA) data were obtained were analyzed by creating ZTE/MRA fusion images and 3D ZTE-based MRI models. We examined whether these images and models can be substituted for computed tomography imaging for neurosurgical procedures. Furthermore, the clinical usability of the 3D ZTE-based MRI models was evaluated by comparing them with actual surgical views. Results: Zero-echo-time/MRA fusion images and 3D ZTE-based MRI models clearly illustrated the cranial and intracranial morphology without radiation exposure or the use of iodinated contrast medium. The models allowed determination of the optimum surgical approach to cerebral aneurysms, brain tumors near the brain surface, and cervical internal carotid artery stenosis by visualizing the relationship of lesions with adjacent bone structures. However, ZTE-based MRI did not provide useful information for surgery for skull base lesions such as vestibular schwannoma because bone structures of the skull base often include air components, which cause signal disturbance in MRI. Conclusions: Zero-echo-time sequences on MRI allowed distinct visualization of not only bone but also vital structures around the lesion. This technology has low invasiveness for patients and was useful for preoperative planning and guidance of the optimum approach during surgery in a subset of neurosurgical diseases.